Catalysis of Enantioselective Strecker Reaction in the Synthesis of D‐Homophenylalanine Using Recyclable, Chiral, Macrocyclic MnIII–Salen Complexes. Issue 6 (12th April 2013) - Saravanan, S.; Khan, Noor‐ul H.; Bera, Prasanta K.; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Kumari, Prathibha; Bajaj, Hari C.
Abstract A convenient approach to the asymmetric Strecker reaction was established by synthesizing chiral, mono‐ and dinuclear, macrocyclic MnIII–salen complexes possessing achiral and chiral linkers (trigol, piperazine, and diethyl tartarate). This group of macrocyclic complexes has emerged as improved metal‐based catalysts for the enantioselective Strecker reaction of aldimines, giving high enantioselectivity (up to 99 %) for a wide range of substrates. The macrocylic complex 6 a with trigol linker works very well with TMSCN (trimethylsilyl cyanide) as a source of cyanide, using 4‐phenyl pyridine N‐oxide (4‐PPyNO) as a co‐catalyst in toluene at −40 °C. However, the macrocyclic complex 6 b with diethyl tartarate as a linker affected excellent chiral induction for both aromatic and aliphatic imines with a safer cyanide source (ethyl cyanoformate) in toluene at −20 °C in the presence of N, N‐diisopropylimine as a co‐catalyst. Complexes 6 a and 6 b used in the present study were recoverable and recyclable (five times) with retention of their performance at gram level. The kinetic study with complex 6 a for the enantioselective Strecker reaction of N‐benzyl benzylimine revealed a first‐order dependence on catalyst, substrate, and TMSCN concentration. This protocol with catalyst 6 b was further extended for the synthesis of D‐homophenyl alanine, an important analogue in factor Xa inhibitors.